Implementasi Kegiatan Outdoor Study dalam Proses Pembelajaran di SD Negeri Jirapan 4 Masaran Sragen - Sari, Tiara Ratna; , Minsih, S.Ag., M.Pd (2017)
This study aims to: 1) To describe the teacher in designing outdoor learning activities in the learning process in SD Negeri Jirapan 4 Sragen; 2) To describe outdoor learning activities in the learning process at SD Negeri Jirapan 4 Sragen; 3) To describe the influence of outdoor learning activities in the learning process in SD Negeri Jirapan 4 Sragen. . This type of research is qualitative research with case study design. Informants in this study were principals, teachers and students. Data collection techniques used are observation, interviews, and documentation. The validity of this research data using source triangulation. The results showed that in the implementation of outdoor learning activities in the learning process in SD Negeri Jirapan 4 Sragen in perencanaa learning activities of teachers to observe PROTA, PROMES, and syllabus in preparing RPP and appropriate learning media. In the implementation of outdoor study, the students' eyes that can be applied are SBK, Bahasa Indonesia, Mathematics, Science, Social Studies and Civics. Outdoor study activities are also able to develop the character of students, among others: discipline, responsibility, confident, independent, creative, religious, honest, tolerance, hard work, democratic, spirit, nationality, love homeland, appreciate achievement, love peace Social, and certainly care about the environment.